Penerapan Aspek Keadilan Dalam Pengadaan Tanah Untuk Kepentingan Umum di Indonesia - Arvin Asta Nugraha; Lego Karjoko; Rahayu Subekti (Faculty of Law Universitas Sebelas Maret Surakarta, 2022)
This research aims to analyze the application of aspects of justice in the process of implementing land procurement for the public interest in Indonesia. The research method used in is a normative juridical method that is prescriptive. The results of the study can be concluded that, first aspect of justice is something that must be applied in land procurement by providing fair and decent compensation that not only assesses physical losses but assesses non-physical losses also need to be taken into account with reference to laws and regulations. Both concepts of fair and decent compensation are intended so that affected communities or communities whose land rights are revoked can live their lives or even better. For those who refuse the amount of damages are given the right to be able to submit an objection to the District Court then to the Supreme Court if it still objects to the decision from the District Court. The application of justice in the procurement of land in the public interest is to ensure the sustainability of the productivity of communities affected by land procurement so that they can work in the period of fulfillment of their lives and their families to achieve the welfare of life.